Obtenção, caracterização e atividade antiviral de B-D-Glucana microbiana sulfatada contra o vírus sincicial respiratório (RSV)) - Silva, Alaor Martins da (2024)
β-glucans are macromolecules with clinically and biotechnologically relevant biological properties. Chemical modification in the primary structure of these biopolymers canenhance or confer new biological properties. Sulfated derivatives of β-D-glucan (Lasiodiplodan) produced by the ascomycete Lasiodiplodia theobromae MMPI were obtained and characterized by Fourier Transform Infrared Spectroscopy (FTIR), Thermal Analysis (TGA/DTG and DTA), X-ray Diffraction (XRD), and Scanning Electron Microscopy (SEM). Antimicrobial, antioxidant, and antiviral activities against Respiratory Syncytial Virus (RSV) were also evaluated. Two sulfated derivatives with DS of 0.11 (LAS-S1) and 0.51 (LAS-S2) were obtained. The introduction of a greater number of sulfate groups in the molecule (LAS-S2) contributed to increased solubility, both in water and organic solvent (DMSO). Absorption bands in the infrared spectrum at 1220 cm-1 (S=O stretching vibration) and 800 cm-1 (C-O-S bending vibration) indicated the sulfation of β-glucan. Sulfation demonstrated effects on the thermal stability of the macromolecule, contributing to an increase in the number of mass loss events in the derivative with higher DS. Similarly, the sulfation enhanced the antioxidant activity of β-glucan, especially regarding the capacity to eliminate hydrogen peroxide (H2O2). Likewise, sulfation proved to be an important mechanism for obtaining molecules with virucidal activity against Respiratory Syncytial Virus (RSV). The results suggest that sulfation may be a promising strategy for enhancing the biological functionalities of lasiodiplodan, enabling new biotechnological and pharmaceutical applications.